PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Octanli, Artavia; Sha, Thio Lie (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study was to obtain empirical evidence regarding the effect of liquidity, leverage, profitability, and firm size on firm value. The sample data used were 63 companies using purposive sampling method. This study uses secondary data. Data processing using Microsoft Excel 2019 and Eviews version 12. The research results show that profitability has a positive and significant effect on firm value, while leverage and firm size have a positive and insignificant effect on firm value. Liquidity has a negative and insignificant effect on firm value. The implication of this research is that the company's performance is very important to increase the company's profit and value.